2020
DOI: 10.1002/mrm.28273
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of implanted carbon electrodes for electromagnetic field mapping during neuromodulation

Abstract: Purpose Deep brain stimulation electrodes composed of carbon fibers were tested as a means of administering and imaging magnetic resonance electrical impedance tomography (MREIT) currents. Artifacts and heating properties of custom carbon‐fiber deep brain stimulation (DBS) electrodes were compared with those produced with standard DBS electrodes. Methods Electrodes were constructed from multiple strands of 7‐μm carbon‐fiber stock. The insulated carbon electrodes were matched to DBS electrode diameter and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Implantable DBS leads and electrodes were imaged in two studies, and one study reported following ASTM International standards. All components had temperature increases <1 °C when tested in phantom models 28,29 . Ashok Kumar et al imaged carbon electrodes and reported a lower temperature increase of 0.1 °C compared to 0.9 °C when traditional platinum‐iridium electrodes were used 29 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantable DBS leads and electrodes were imaged in two studies, and one study reported following ASTM International standards. All components had temperature increases <1 °C when tested in phantom models 28,29 . Ashok Kumar et al imaged carbon electrodes and reported a lower temperature increase of 0.1 °C compared to 0.9 °C when traditional platinum‐iridium electrodes were used 29 …”
Section: Resultsmentioning
confidence: 99%
“…All components had temperature increases <1 °C when tested in phantom models 28,29 . Ashok Kumar et al imaged carbon electrodes and reported a lower temperature increase of 0.1 °C compared to 0.9 °C when traditional platinum‐iridium electrodes were used 29 …”
Section: Resultsmentioning
confidence: 99%
“…With MREIT, DBS current flow and electric field distributions can be measured, providing information about stimulation through target tissues and around brain structures. This information could then be used to further our understanding of the mechanisms underlying DBS 16 …”
Section: Electrode Geometriesmentioning
confidence: 99%
“…Pulse generators that have the ability to modify the pulse width are available in newer models and compatible electrodes 13 . The amplitude is easier to manipulate with most IPGs, and is tuned to the range of 1 V to 5 V 16 . Increased amplitude does not result in higher clinical benefit, but decreased pulse width can increase the therapeutic window.…”
Section: How Dbs Workmentioning
confidence: 99%
See 1 more Smart Citation